Barriers and Enablers for Adolescents Accessing Substance-Use Treatment: A Systematic Review and Narrative Synthesis. - Comiskey, Catherine; Nash, Michael; James, Philip (My University, 2024)
Substance use is a persistent concern for adolescents in many countries due to the significant negative impact on mental, physical and social outcomes. US research indicates that while 4.1% of 12–17-year-olds require treatment, <10% of those who require it access it. This paper summarises the literature available on the barriers and enablers to those under 18s attending substance use treatment to inform policy and practice. Using a systematic approach, we searched six databases for studies which reported barriers and enablers to those aged 18 and under accessing substance use treatment. Thirty-two papers met the inclusion criteria and we present the findings using a narrative synthesis. Only one paper identified explored this topic in Europe. Barriers and enablers are presented across four themes: (1) individual factors, (2) societal factors, (3) Gateway Providers and (4) treatment service factors. Mental health nurses, especially those working with young people, should be aware that adolescents are unlikely to perceive their substance use as problematic and rely on adults to access treatment. Access appears more difficult for females and socially marginalised youth. Various professionals direct young people towards treatment, but clear protocols are needed to encourage them to intervene, which could be an opportunity for nurses to be innovative and lead in this area. Services perceived as adolescent-specific, youth-friendly and flexible encourage attendance while the cost of treatment, including time off work and transport, function as barriers.
PUBLISHED
Keywords: Addiction and substance abuse; Mental health nursing